Association of genetic polymorphisms and their attributing factors with lipid profiles among outpatient statin users in Hospital USM - Shamsudin, Amirul Faez (2022)
Statins, or 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors, are routinely used to lower lipid levels primarily low-density lipoprotein cholesterol (LDL-c). Treatment guidelines recommend LDL-c as the primary target of therapy in hyperlipidaemic patients. Inter-individual variation in LDL-c-lowering efficacy and side effects of statins are due to genetic polymorphisms and environmental factors. However, pharmacogenetics studies on the effects of the aforementioned factors on the lipid profiles of statin users in Malaysia are still lacking. We evaluated the association of patient’s genetic polymorphisms, demographic profiles, and clinical factors with lipid profiles among outpatient statin users from Hospital Universiti Sains Malaysia (HUSM). In a cross-sectional retrospective study, a total of 229 hyperlipidaemic statin users were recruited and the patients' genotypes for eight single nucleotide polymorphisms (SNPs) in seven candidate genes were determined using the polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP) method and validated by sequencing analysis. Using a dominant genetic model, an independent t-test was used to compare total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c), LDL-c and triglycerides (TG), and the results with significant differences were stratified according to gender. A multiple binary logistic regression model was conducted, with LDL-c < 2.6 mmol/L at the endpoint serving as the dependent variable while other explanatory factors as independent variables. Minor allele frequency (MAF) of the studied SNPs as follow; CETP rs708272 = 0.39, ABCG2 rs2231142 = 0.12, ABCC2 rs717620= 0.58, APOE E4 = 0.35, GATM rs9806699 = 0.63, COQ2 rs4693075= 0.96, and APOA5 rs662799= 0.45. Only CETP rs708272 and COQ2 rs4693075 were matched to the MAF of the reference population (i.e., East Asian populations) obtained from the ENSEMBLE database (P>0.05). Of all SNPs genotyped, two SNPs (CETP rs708272 and ABCG2 rs2231142) were associated with baseline lipid parameters. At the baseline before statin treatment, female minor allele carriers of CETP rs708272 were associated with higher LDL-c (4.02 ± 1.44 mmol/L vs 3.44 ± 0.84 mmol/L, P=0.007) and lower TG levels (1.52 ± 0.63 mmol/L vs 1.90 ± 0.98 mmol/L, P=0.044). ABCG2 rs2231142 was associated with higher HDL-c levels in both overall (1.38 ± 0.37 mmol/L vs 1.25 ± 0.26 mmol/L, P=0.035) and females group (1.49 ± 0.38 mmol/L vs 1.33 ± 0.27 mmol/L, P=0.047). After the initiation of statin treatment, two SNPs (ABCC2 rs717620 and APOA5 rs662799) were associated with anti-atherogenic effects. In particular, ABCC2 rs717620 was associated with significant reduction of TG levels in the overall (1.48 ± 0.75 mmol/L vs 2.17 ± 1.14 mmol/L, P=0.009) and males group (1.48 ± 0.85 mmol/L vs 2.40 ±0.91 mmol/L, P=0.006). Similarly in males, minor allele carriers of APOA5 rs662799 resulted in higher HDL-c (1.20 ± 0.25 mmol/L vs 1.07 ± 0.15 mmol/L, P=0.006) and lower TG levels (1.42 ± 0.81 mmol/L vs 1.69 ± 0.75 mmol/L, P=0.038). In the multiple binary logistic regression analysis, only pravastatin users independently predicted patient’s achieving LDL-target of <2.6 mmol/L (P=0.040, OR=0.110). In conclusion, CETP rs708272 and ABCG2 rs2231142 determined the baseline lipid differences in females, whereas ABCC2 rs717620 and APOA5 rs662799 determined the lipid differences after statin initiation in males group.